2021
DOI: 10.1177/08850666211032175
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corticosteroids on Secondary Infection and Mortality in Critically Ill COVID-19 Patients

Abstract: Background: Corticosteroids are part of the treatment guidelines for COVID-19 and have been shown to improve mortality. However, the impact corticosteroids have on the development of secondary infection in COVID-19 is unknown. We sought to define the rate of secondary infection in critically ill patients with COVID-19 and determine the effect of corticosteroid use on mortality in critically ill patients with COVID-19. Study Design and Methods: One hundred and thirty-five critically ill patients with COVID-19 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Likewise, a recent systematic review revealed that 53% of CAPA patients were on steroid therapy; therefore, a hypothetical correlation was suggested to exist between steroid use and the development of CAPA infection [79,80]. Ritter et al 2021 challenged this hypothesis through their single-centre experience, as they found that the hazard ratio of secondary infections due to corticosteroid administration was only 1.45 (CI 95%: 0.75-2.82; p = 0.28) among critically ill COVID-19 patients; therefore, they recommended that corticosteroids as an effective therapy for COVID-19 should not be discontinued due to the suspicions of secondary infection [81].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a recent systematic review revealed that 53% of CAPA patients were on steroid therapy; therefore, a hypothetical correlation was suggested to exist between steroid use and the development of CAPA infection [79,80]. Ritter et al 2021 challenged this hypothesis through their single-centre experience, as they found that the hazard ratio of secondary infections due to corticosteroid administration was only 1.45 (CI 95%: 0.75-2.82; p = 0.28) among critically ill COVID-19 patients; therefore, they recommended that corticosteroids as an effective therapy for COVID-19 should not be discontinued due to the suspicions of secondary infection [81].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of VAP in patients with COVID-19 has varied from 40 to 60% [ 13 , 14 , 18 ]. This range is higher than in patients with ARDS not related to COVID-19 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are occurrences of secondary bacterial infections that came with tocilizumab use but these cases had not led to deaths [63]. The corticosteroids in contrast, despite their immune-modulating action, seldom led to secondary infections but may cause hyperglycemia and may potentially lead to the onset of diabetes [64][65][66]. But weighed against the almost equal benefits of both drugs and the combination of the two in COVID-19 mortality reduction as seen in this review, their use as key COVID-19 treatment modalities is strongly justified.…”
Section: Discussionmentioning
confidence: 99%